Continuous professional growth: A study of educators' commitment to lifelong learning - Musa, Safuri; Suherman, Ade Maman; Sujarwo, Sujarwo; Nurhayati, Sri (Jurnal Cakrawala Pendidikan, 2024)
This research explores the commitment of Indonesian educators to Continuous Professional Growth (CPG) and lifelong learning. With the rapidly changing educational landscape, educators must adapt to emerging pedagogical trends, harness new technologies, and lead both inside and outside the classroom. This study utilized a qualitative case study approach, encompassing semi-structured interviews, classroom observations, and document analysis, to deeply understand ten driving school educators' experiences, perceptions, and motivations regarding lifelong learning in Indonesia. Findings indicate educators' involvement in teacher selection, school development, and digital transformation. Their dedication to innovation, feedback, collaboration, and skill development, especially in technology and instructional approaches, underscores their commitment to continuous growth. The study emphasizes the multifaceted nature of educators' lifelong learning journeys and the importance of adaptability, collaboration, and technology in modern education.